No-place and urban space in Haruki Murakami’s novels - Hoe, Siang Yee (2018)
Haruki Murakami's works are widely read by modern-day readers situated in dense urban spaces. Looking at urban spaces in new perspectives through the lens of psychogeography, this paper serves to explore the rediscovery of not only the urban spaces, but also its relations to the individuals situated within them. This will be done through the literary criticism of representations in Murakami's novels, namely Norwegian Wood, Sputnik Sweetheart and Hard-Boiled Wonderland and the End of the World. Overlooking the ambiguity of translation, the paper argues for a sensitivity towards these urban spaces and the location of contemporary selves within and in response to them, especially in an ever-changing urban landscape.